The profitability of Japanese yen carry trades - Czech, Katarzyna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The aim of the paper is to examine the profitability of Japanese yen carry trade strategies. It has been shown that for the sample of 11 years, annualized excess return of carry trade strategies are positive. Estimated average excess returns, Sharpe ratio and Calmar ratio turn out to reach the levels similar to those reported by other researchers. Moreover, the paper reports that estimated excess returns and Sharpe, Calmar ratios are high and positive during the period from 01.2006 to 07.2007 and negative during the time of high financial turbulence. Additionally, during the time of turbulence in financial markets, when carry trade performs poorly, low-yielding currencies tends to appreciate against high-yielding currencies. It implies that Japanese yen, as an example of the most popular funding currency, may provide a hedge during unstable times of high price volatility in financial market
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 486, s. 245-253
Keywords: foreign exchange markets; carry trade; Japanese yen; Sharpe ratio; Calmar ratio; rynek walutowy; jen japoński; wskaźnik Sharpe’a; wskaźnik Calmara